Examining the meaning of space as a relational actor in drug use experience - Kordalı Takak, Gizemnur; Şaşman Kaylı, Derya; Cengisiz, Cengiz (Journal of Dependence, 2025)
Objective: This research aims to understand how and why places become meaningful for individuals in substance use experiences. Method: Within the scope of this study, which was designed with a phenomenological qualitative design, in-depth interviews were conducted with 20 participants who were being treated in Manisa Decontamination Centre due to substance use experience, and the information obtained was analysed within the framework of relational space understanding with content analysis technique. Results: The findings reveal the existence of certain dynamics that make spaces conducive or unfavorable for substance use. While elements of insecurity, secrecy, belonging and pressure are prominent in spaces conducive to use, spatial dynamics related to substance withdrawal are associated with horizontal relations, flexible rules, shared experiences and routine-building practices in treatment spaces. Conclusion: The research has the potential to contribute to social policies in the fight against substance abuse by providing in-depth information on preferences, interactions, boundaries and actions related to substance use.